2019
DOI: 10.1108/ejtd-09-2018-0091
|View full text |Cite
|
Sign up to set email alerts
|

Pigeonholing or learning instrument?

Abstract: Purpose While factors that influence test takers’ reactions to personality testing in selection contexts have been well researched, little empirical research evidence exists to determine whether these factors also apply to test takers’ reactions in the context of management development (MD). The purpose of this study is, therefore, to explore what explains different test takers’ reactions in the context of MD programs. Design/methodology/approach A qualitative longitudinal approach with three phases of data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…Various neutral reactions were reported. Some claimed that trainees often forget their personality feedback shortly after the training or never mention it again (Boas, 1996;Coe, 1991Coe, , 1992Lundgren et al, 2019). Some trainees reported that the workshop had no apparent effect on work behavior or group dynamics (Clinebell & Stecher, 2003;Sutton et al, 2015).…”
Section: Outcomes Of Personality-based Trainingsmentioning
confidence: 99%
See 4 more Smart Citations
“…Various neutral reactions were reported. Some claimed that trainees often forget their personality feedback shortly after the training or never mention it again (Boas, 1996;Coe, 1991Coe, , 1992Lundgren et al, 2019). Some trainees reported that the workshop had no apparent effect on work behavior or group dynamics (Clinebell & Stecher, 2003;Sutton et al, 2015).…”
Section: Outcomes Of Personality-based Trainingsmentioning
confidence: 99%
“…In some cases, trainees may not know the purpose of these trainings (Jelley, 2021). One trainee reported, “It is something [organizational leaders] have invested money in but never really told us how to use” (Lundgren et al, 2019, p. 364). Moreover, there is no static set of learning objectives, because many training interventions are customized for clients.…”
Section: Terminologymentioning
confidence: 99%
See 3 more Smart Citations